Secure cloud‐based data storage scheme using postquantum integer lattices‐based signcryption for IoT applications. Issue 9 (27th May 2022) - Dharminder, Dharminder; Kumar, Uddeshaya; Das, Ashok Kumar; Bera, Basudeb; Giri, Debasis; Jamal, Sajjad Shaukat; Rodrigues, Joel J. P. C.
Abstract: The primary objective of postquantum cryptography (also known as quantum‐resistant cryptography) is to develop the cryptographic systems that need to be robust against both quantum and classical computers, and can also interoperate with the existing communications protocols and networks. In an Internet of Things (IoT) environment, the communicated messages contain sensitive information that are transmitted over an open channel, where message integrity and data privacy become challenging tasks. Although several traditional cryptographic security protocols can be applied for IoT security and data privacy, such as authentication, access control, key agreement, and digital signature, but they are not resilient against quantum attacks. To overcome these issues, in this article, we first present an advanced and efficient construction of postquantum lattice‐based signcryption scheme, and then apply the constructed lattice‐based signcryption in IoT applications, where data sensed by the deployed IoT smart devices is securely stored at the cloud, via the gateway nodes (aggregators). The data stored at the cloud servers cannot be even modified by them due to the involved signatures generated by the aggregators. The formal security analysis shows the robustness of our designed lattice‐based signcryption scheme. Other detailed information security analysis and a performance analysis with the traditional number‐theoretical based public key cryptosystems show the efficacy, and significantly better security and functionality features of the proposed scheme under the lattice‐based postquantum context. Abstract : We first present an advanced and efficient construction of signcryption scheme in some random lattice satisfying strong security without random oracles. Next, we apply the constructed latticebased signcryption in Internet of Things (IoT) applications for secure cloud based data storage in IoT applications (SCDS‐LBSIoT). A comparative analysis with the traditional number‐theoretical based public key cryptosystems shows that the proposed scheme requires low communication and compuational overheads, and offers significantly better security and functionality features under the lattice‐based post quantum context.